The Influence of Pregnant Women's Motivation on The Detection of Danger Signs of Pregnancy - Isabelita Madeira Soares; Agustin Widyowati; Lidia Gomes (Jurnal Ilmiah Multidisiplin Keilmuan Mandira Cendikia, 2024)
Early detection of danger signs of pregnancy is very important to prevent complications that can endanger the health of the mother and fetus. Motivation of pregnant women plays a crucial role in increasing the ability to recognize and respond to these danger signs. This study aims to identify the influence of pregnant women's motivation on the detection of danger signs of pregnancy through a systematic literature review (SLR). This research uses the SLR method by collecting and evaluating relevant literature from various databases, including PubMed, Scopus, and Google Scholar. The selected articles were those published within the last 10 years and studied the influence of motivation on the detection of danger signs of pregnancy. The article was analyzed using qualitative methods for narrative synthesis. The findings show that high motivation in pregnant women, supported by comprehensive health education, social support, and easy access to information, significantly increases the ability to detect danger signs of pregnancy. Research involving the use of social media, websites, and audiovisual media shows increased knowledge and awareness of pregnant women. Support from husbands and families has also been proven to increase pregnant women's awareness of the risks of pregnancy. However, the variability of results between studies suggests that socio-economic factors and access to health services play an important role in influencing pregnant women's motivation. Motivation of pregnant women is very influential in increasing the ability to detect danger signs of pregnancy. Increasing health education, social support, and the use of information technology must be the focus of policy and clinical practice to improve maternal health. By applying these findings, it is hoped that we can reduce the risk of pregnancy complications and improve maternal and infant health outcomes